Effect of the self-healing properties of asphalt mixture on the interlayer shear performance of bridge deck pavement. (16th May 2023) - Li, Jia; Fan, Siyuan; Zhang, Henglong; Chen, Zihao; Li, Qishi; Xiao, Peng
Highlights: The self-healing properties of the STC-SMA composite bridge deck pavement were investigated. Interlayer failure and recovery mechanism of rigid-flexible composite pavement was discussed. Correlation between the healing indexes of the monotonic test and the cyclic test was analyzed. Abstract: By conducting the monotonic and cyclic direct shear tests under different healing conditions, the interlayer performance and healing properties of the STC (Super Toughness Concrete)-SMA (Stone Matrix Asphalt) were investigated. Healing properties of the STC-SMA with two different asphalt binders under various healing conditions were assessed. Two different indexes were used to evaluate the healing efficiency of the STC-SMA in both the monotonic and cyclic direct shear tests. The findings indicate that the failure pattern between the STC and SMA is that asphalt is stripped out of the aggregates. The interlayer shear resistance is restored to different degrees under different healing conditions, and extending the healing time or increasing the healing temperature under a certain range promotes the healing rate of the asphalt mixture. Healing efficiency of the STC-SMA interlayer decreases gradually as the healing time increases. Interlayer healing performance of the specimen using the SBS (Styrene-Butadiene-Styrene)-modified asphalt is superior to those of high viscosity asphalt. Results of the monotonic direct shear test is less sensitive to healing conditions than the cyclic direct shear test. Healing conditions significantly affect the adhesion strength of asphalt binder and aggregates, which is directly relate to the decrease rate of the shear stiffness modulus of the healed STC-SMA specimen. For the same asphalt, there is a high correlation between the healing indexes of the monotonic direct shear test and the healing indexes of the cyclic direct shear test.